DESIGN OF GENSET MONITORING & RECORDING EQUIPMENT WITH THE CONCEPT OF INTERNET OF THINGS (IOT) BASED ON ARDUINO UNO - Atmiasri; Sizka Novita Dewi (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2023)
Generators are widely used in offices, hospitals and companies that require a 24-hour electricity supply. Generators are often used to replace the main power supply from PLN in the event of a power outage. The purpose of this thesis is to make it easier for technicians to monitor the condition of the output from the generator, namely current, voltage, and rotational speed (RPM) with a monitoring and recording system that can work remotely. With the existence of a system of monitoring and recording remotely via a personal computer that can streamline the technician's time. Arduino uno as a data processing center that is integrated with the database. The monitoring and recording system on the generator is activated by connecting Wifi then this arduino gets input from the current, voltage and rotational speed sensors (RPM) the data will be processed with the arduino uno according to the data created on the system. This system is also displayed using Bylnk via a personal computer.